Analisis Bibliometrik Good Government Governance di Indonesia dari Tahun 2015-2020 - Dri Asmawanti-S; Melin Soya (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
This study aims to map the research topics carried out by “Good Government Governance” researchers. Identify some research variations in terms of keyword, definitions, theories, methodologies, citation, publication year, and research result. Also, provide suggestions for further research. The data used are secondary data. The number of samples in this study were 58 articles about “Good Government Governance”. The data collection technique used the literature study technique in the form of direct observation of articles and books with the bibliometric analysis method using three special applications of bibliometric analysis. The data analysis method used is bibliometric analysis with Publish or Perish, Mendeley, VOSviewer with tables and graphs using the Microsoft Office Excel program. The results of this study indicate that the vosviewer mapping shows that there are 5 clusters that discuss the topic of “Good Government Governance”, definition of Good Government Governance, Quantitative research methodology, the definition of Good Government Governance, dominating theory is the Agency Theory and Stewardship Theory. The implication of the results of this study can be used for practitioners who are expected to provide a reference for academics such as students, lecturers or teaching accountants who will conduct research using bibliometric analysis in accordance with current issues